2019
DOI: 10.1002/art.40730
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Genetic Contribution to Variation in Posttraumatic Osteoarthritis in Mice

Abstract: For these mouse strains, various characteristics of PTOA varied with genetic composition demonstrating a genetic basis for PTOA susceptibility. The heritability of PTOA was established. Phenotypes exhibited various degrees of correlations: (1) cartilage degeneration is positively correlated with synovitis, but (2) not with the formation of ectopic calcification. Further investigation of the regions of genome containing genes implicated in OA and expression data will be useful for studying mechanisms of OA and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 57 publications
3
31
1
Order By: Relevance
“…Recent studies also reported that Postn levels in synovial fluid correlate with radiographic signs of knee OA [41], and that Postn is the only protein whose expression levels significantly correlate with OARSI score, synovitis, and microCT-based bone parameters (e.g., Structure Model Index and trabecular threshold). Postn influences ECM homeostasis, bone remodeling, and OA development [42]. Therefore, Postn offers a unique target for OA treatment since it can mediate pathogenic events in both cartilage and bone.…”
Section: Plos Onementioning
confidence: 99%
“…Recent studies also reported that Postn levels in synovial fluid correlate with radiographic signs of knee OA [41], and that Postn is the only protein whose expression levels significantly correlate with OARSI score, synovitis, and microCT-based bone parameters (e.g., Structure Model Index and trabecular threshold). Postn influences ECM homeostasis, bone remodeling, and OA development [42]. Therefore, Postn offers a unique target for OA treatment since it can mediate pathogenic events in both cartilage and bone.…”
Section: Plos Onementioning
confidence: 99%
“…Interestingly, the "super-healer" MRL/MpJ mice are resistant to cartilage damage and show reduced severity of PTOA when compared to C57BL/6 mice, whether following surgical DMM [22] or non-surgical IAF [88]. Similar results are seen in the LG/J strain [34], whereas p21 −/− mice seem to be vulnerable to cartilage damage following DMM surgery [89], despite its superior regenerative potential after full-thickness cartilage injury [49].…”
Section: Models Of Oa and Cartilage Damagementioning
confidence: 70%
“…Various animal models have been employed in cartilage injury and OA-related studies, including mice, rats, guinea pigs, rabbits, dogs, and larger animals such as goats and horses [30][31][32][33][34][35][36]. Each animal model presents advantages and limitations in terms of their cost-benefit, suitability to mechanistic and molecular studies, and translational potential (i.e., relevance to human OA), all of which have been previously reviewed [35,37].…”
Section: Diversity Of Regenerative Potential Across Animal Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Firstly, DMM and age-induced OA models were established, which are extensively studied in OA, while limitations also exist in these two models. DMM model is defined as one of the most usual-used OA models, which have lesions primarily on the central weight-bearing region of the medial tibial plateau and medial femoral condyles, and have no destruction of the subchondral bone [72,73]. However, it can still not naturally reflect human osteoarthritis, which makes it hard to allow the whole disease process to be studied.…”
Section: Discussionmentioning
confidence: 99%